1989
DOI: 10.1037/0022-0663.81.4.610
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory models in the processing of science text: The role of prior knowledge activation through small-group discussion.

Abstract: Two experiments assessed effects of activation of prior knowledge through small-group discussion. Subjects were given a description of natural phenomena and were asked to elaborate on possible explanations for them. In Experiment 1, small groups of subjects were presented with a problem describing the behavior of a blood cell in pure water and in a salt solution. No additional text was studied. The experimental subjects produced more than twice as many propositions about osmosis (i.e. the biological process ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
124
1
3

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(130 citation statements)
references
References 35 publications
0
124
1
3
Order By: Relevance
“…As mentioned earlier, the results of some studies suggested that collective elaborative activities can improve the processing of new information, so information that is studied after the elaborative activities took place (O'Donnell et al 1990;Schmidt et al 1989;De Grave et al 2001). This study aimed to replicate these findings, while zooming in on the role of providing explanations versus listening.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…As mentioned earlier, the results of some studies suggested that collective elaborative activities can improve the processing of new information, so information that is studied after the elaborative activities took place (O'Donnell et al 1990;Schmidt et al 1989;De Grave et al 2001). This study aimed to replicate these findings, while zooming in on the role of providing explanations versus listening.…”
Section: Introductionmentioning
confidence: 94%
“…Interestingly, elaborative discourse has also been shown to be beneficial when it precedes learning (De Grave et al 2001;O'Donnell et al 1990;Schmidt et al 1989). In a study by Schmidt et al (1989), small groups of students discussed a problem illustrating the osmosis process in cells before studying a text about osmosis and diffusion. These students recalled more information from the text than students who had discussed a non-relevant problem, about airplanes taking off, before studying the same text.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elaborations can occur in group learning situations when learners consider pieces of knowledge in richer and wider contexts (van Boxtel, van der Linden, & Kanselaar, 2000). It has been found that in PBL, elaboration is an important contributor of cognitive effects (Schmidt & Boushuizen, 1993;Schmidt, De Volder, De Grave, Moust, & Patel, 1989).…”
Section: Socio-cognitive Processes In Pblmentioning
confidence: 99%
“…Así mismo, por lo que respecta al papel del conocimiento previo, es claro que los sujetos expertos en un tema, independientemente de su edad, recuerdan más que los novicios, además de tener un recuerdo mejor organizado (Chiesi, Spilich y Voss, 1979;Pearson, Hansen y Gordon, 1979;Recht y Leslie, 1988). Así mismo, cuando el conocimiento previo es activado previamente al estudio de un texto, ello mejora el recuerdo de proposiciones que presumiblemente reflejan la formación de un modelo mental adecuado, tanto en el caso de los sujetos expertos como en el de los novicios (Schmidt et al, 1989). En el caso del aprendizaje de las ciencias hay que resaltar la necesidad de partir de las concepciones previas o preconceptos de los alumnos, hacer conscientes a los estudiantes de dichas concepciones y promover el cambio conceptual para conseguir un aprendizaje efectivo, lo cual está estrechamente ligado a la consecución de un modelo situacional adecuado (p.e., Driver, 1988;Pozo, 1989).…”
unclassified